LITERATURE STUDY ON THE ROLE OF ISLAMIC FINANCIAL INSTITUTIONS IN MSME EMPOWERMENT - Kamaruddin Kamaruddin; Andri Soemitra (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The efforts to develop and empower MSMEs (Micro, Small and Medium Enterprises) have always been an important assignment for the government. This is considering that the micro, small and medium business sector has a big role in the national economy. This research methodology was of qualitative research using a literature study approach aimed to answer research. This literature study was conducted by collecting journals and articles according to the theme of the research objectives. Data obtained from journals and articles would be continued to data reduction process by drawing conclusions or verification. The main finding of this research is that the Islamic Microfinance Institution (IMI) is the channel of funds to MSME business actors. Financing growth strengthens the intermediation function of financial institutions. The amount of financing describes the potential of funds that can encourage MSME activity and growth.